Formation of a personnel management system as a factor of increasing competitiveness and the enterprise security level in the context of digital transformation and new legal challenges - Kopytko, Marta; Liubokhynets, Larysa; Panchenko, Volodymyr; Moysa, Taras; Malanchuk, Anton (Social & Legal Studios, 2024)
The relevance of the subject of forming a personnel management system in the context of the problem of increasing the competitiveness and level of security of enterprises lies in the need to adapt to the challenges of digital transformation and growing internal and external threats. The purpose of the study is to present a modern approach to the formation of an effective personnel management system, considering the emphasis on countering internal threats and ensuring the rights of workers. The research methodology involves the use of the expert analysis method for identifying key threats (the Delphi method as an auxiliary one), the hierarchical analysis method for organising threats and paired comparison for comparing threats. As a result, a list of the most substantial threats to the formation of the personnel management system is presented. Calculations determined that in the second half of the 2020s, the impact of internal threats on the personnel management system and the competitiveness of enterprises is expected to increase, which may negatively affect the provision of labour rights. It is established that the formation of a personnel management system is a complex process that is influenced by various factors and threats. Analysing threats through the prism of this theoretical and methodological framework, it is identified that not only the identified threats are critical, but also the dynamics of their development and interaction are crucial for the development of personnel management strategies. It was established that the complex impact of these threats requires not only a one-time response but also continuous adaptation of the personnel management system. The study highlights the importance of countering internal threats, which is crucial for ensuring enterprise security. The practical application of the research results can help businesses create a stronger and safer work environment that will help ensure workersʼ rights